Anticancer potential of Thymoquinone from Nigella sativa L.: An in-silico and cytotoxicity study. - Yathendranaik Ravi; Periyanadar Irene Vethamoni; Shailendra Nath Saxena; Muthusamy Kaviyapriya; Vichangal Pridiuldi Santhanakrishnan; Muthurajan Raveendran; Narayana Naik Ashoka; Sharda Choudhary; Arvind Kumar Verma; Chowdasandra Byregowda Harisha; Palanisamy Dhamotharan; Vinay Bhardwaj (PLoS ONE)
Nigella sativa L. widely used spice cum medicinal plant in Asia and the middle east, is renowned for its seeds and oil which possess both culinary and therapeutic purposes. Its rich content of bioactive compounds, including metabolites and phenolics, with Thymoquinone, a monoterpene quinone, emerging as key therapeutic compound significantly consideration for its various pharmacological activity with lower toxicity compared to conventional chemotherapy. This study evaluated the anticancer potential of thymoquinone isolated from N. sativa L., through cytotoxicity and In Silico studies. Seeds from 38 accessions were collected across the country and screened for Thymoquinone content using HPTLC with the highest concentration identified in Ajmer Nigella 13 (247.60mg 100gm-1) accession. In Vitro MTT assay of Thymoquinone in human myelogenous leukemia (K562) cells demonstrated significant dose and time dependent cytotoxicity confirming Thymoquinone's potential as a promising therapeutic candidate for leukemia and other cancer.